Biocatalytic synthesis of chiral amine building blocks - Heckmann, Christian M. (2021)
Many commercially important molecules, such as agrochemicals and active pharmaceutical ingredients (APIs), contain chiral amines. However, the synthesis of chiral amines by chemical means is often challenging and in particular in the case of aliphatic amines only low enantiomeric excesses (ees) are achieved. By using enzymes, high pressure hydrogen, high temperatures, precious metals, and organic solvents can often be avoided.